The investigation of state anxiety level of wrestling national team athletes in national team and club competitions - Kul, M.; Görücü, A.; Özal, M.; Yaman, N.; Cetinkaya, E.; Genc, H.; Demirhan, B. (Annals of Ovidius University Constanta-Series Physical Education and Sport/Science, movement and health, 2012)
Objective: The aim of this research is to determine the levels of state anxiety of those athletes who take place in international competitions for national teams and those who take place in the national league competitions for clubs. Methods: 50 national team athletes, whose sport ages are from 1 to 8, participated voluntarily in the study. In order to collect data, personal information forms and Spielberger State Anxiety Inventory were used. Inventory was applied on athletes 20-30 minutes before the competition. Results: According to the results of this study; there obtained significance in sport age state anxiety and, international matches / national league matches state anxiety. On the other hand, there obtained no significance between those athletes who whether won a medal before or not. Conclusion: In conclusion, the national team athletes can administrate their levels of state anxiety better and easier in international matches than league matches.